ANALISIS NOVEL “BUMI MANUSIA” KARYA PRAMOEDYA ANANTA TOER: KAJIAN SEMIOTIKA ROLAND BARTHES (ANALYSIS OF THE NOVEL “BUMI MANUSIA” BY PRAMOEDYA ANANTA TOER: ROLAND BARTHES SEMIOTICS STUDY) - Noor Hanifah (Universitas Lambung Mangkurat, 2022)
Analysis of the novel